2022
DOI: 10.1016/j.spinee.2021.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Spinal arachnoid web—a distinct entity of focal arachnopathy with favorable long-term outcome after surgical resection: analysis of a multicenter patient population

Abstract: Web -a distinct entity of focal arachnopathy with favorable long-term outcome after surgical resection. Analysis of a multicenter patient population.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 36 publications
(55 reference statements)
0
19
0
Order By: Relevance
“…4 Previous studies describe CT myelography as the preferred imaging modality for diagnosing SAWs, but more recent studies have shown that MRI can better identify and localize these entities via visualization of the web as well as regional CSF flow obstruction. 1,11 Current management of SAWs ranges from conservative therapy to surgical resection. Surgical resection is currently the treatment of choice for symptomatic SAWs since it improves neurological symptoms with minimal risk of complication and offers the potential for cure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Previous studies describe CT myelography as the preferred imaging modality for diagnosing SAWs, but more recent studies have shown that MRI can better identify and localize these entities via visualization of the web as well as regional CSF flow obstruction. 1,11 Current management of SAWs ranges from conservative therapy to surgical resection. Surgical resection is currently the treatment of choice for symptomatic SAWs since it improves neurological symptoms with minimal risk of complication and offers the potential for cure.…”
Section: Introductionmentioning
confidence: 99%
“…Current management of SAWs ranges from conservative therapy to surgical resection. Surgical resection is currently the treatment of choice for symptomatic SAWs since it improves neurological symptoms with minimal risk of complication and offers the potential for cure 12 . Those treated conservatively either have mild symptoms that do not warrant surgery or comorbidities that render them poor surgical candidates 1,5,13 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study, Nisson et al 21 concluded that 95% of SAW cases were located dorsally, with 4% located ventrally and 4% located circumferentially. Voglis et al 31 and Nisson et al 21 reported that 100% of SAWs were in the thoracic spine, with 67% and 72% of the patients, respectively, being male. In contrast, Hamilton et al 11 reported a 2:1 female:male predominance.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Hamilton et al 11 reported a 2:1 female:male predominance. Aiyer et al 1 noted that patients' ages ranged from the 4th to 7th decade, while Nisson et al 21 reported a mean age of 52 years, and Voglis et al 31 reported a mean age of 54 ± 12.7 years.…”
Section: Introductionmentioning
confidence: 99%